2003
DOI: 10.1063/1.1631052
|View full text |Cite
|
Sign up to set email alerts
|

Photocurrent mechanism in a hybrid system of 1-thioglycerol-capped HgTe nanoparticles

Abstract: Photoluminescence, absorption, and photocurrent measurements were made for a hybrid system of 1-thioglycerol-capped HgTe nanoparticles synthesized by colloidal method to investigate the photocurrent mechanism in this hybrid system. Absorption and photoluminescence spectra taken for the capped HgTe nanoparticles reveal strong exciton peaks in the near-infrared wavelength range. The wavelength dependence of the photocurrent for these capped nanoparticles is very close to that of the absorption spectrum. For the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 13 publications
0
24
0
Order By: Relevance
“…127 Numerous studies have been carried out using this system, including the synthesis of stable core/shell materials, 76 alloys, 128 investigations into growth conditions, 129 incorporation into emitting devices 130 and photocurrent mechanisms associated with the capping ligand. 131 The seminal investigations into solution routes to HgTe nanomaterials using organometallic precursors were reported by Steigerwald, who used complexes such as Hg(TeR) 2 . 132,133 Thermolysis of the majority of precursor resulted in rapid uncontrolled growth of HgTe; however, the use of a specic precursor, Hg(Te-n-Bu) 2 stopped the reaction proceeding to the bulk material, giving nanoscopic materials.…”
Section: Hge (E ¼ S Se Te)mentioning
confidence: 99%
“…127 Numerous studies have been carried out using this system, including the synthesis of stable core/shell materials, 76 alloys, 128 investigations into growth conditions, 129 incorporation into emitting devices 130 and photocurrent mechanisms associated with the capping ligand. 131 The seminal investigations into solution routes to HgTe nanomaterials using organometallic precursors were reported by Steigerwald, who used complexes such as Hg(TeR) 2 . 132,133 Thermolysis of the majority of precursor resulted in rapid uncontrolled growth of HgTe; however, the use of a specic precursor, Hg(Te-n-Bu) 2 stopped the reaction proceeding to the bulk material, giving nanoscopic materials.…”
Section: Hge (E ¼ S Se Te)mentioning
confidence: 99%
“…Song et al have reported a sonochemical method of synthesizing nanocrystalline HgTe in which ethylenediamine was used as solvent but mixed with a complexing agent of 1-thioglycerol [18]. Wet chemical synthetic routes have also been developed for colloidal HgTe nanoparticles in aqueous solution at room temperature [19][20][21]. …”
Section: Introductionmentioning
confidence: 98%
“…Several methods have been applied for preparation of conventional HgTe materials including the combination of the elements at elevated temperature [13], molecular precursor method [14], and organometallic vapor phase epitaxy growth [15,16]. Recently, vigorous interest has been intrigued by nanometer-scaled HgTe particle because of its quantum confinement effect which can dramatically increase the effective band gap and give rise to near-infrared emission, suggesting prospective applications in 1.3 and 1.5 m optical telecommunication devices [17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…They make the point that although FET measurements are required for practical device demonstrations, they may only reflect the behavior of QDs in a shallow region of QDs close to the gate electrode and may be sensitive to unintentional impurity doping during fabrication, possibly explaining the strong exclusively p-type behavior seen in the earlier sintered film work. Following the earlier work on IR photoconductivity in HgTe QD films [89], Hojun et al [96], extended the IR photoresponse to 1300 nm and compared both lateral and vertical photoconductor device performances. The frequency response of both of these devices was limited to only 100-200 Hz even though the channel lengths were quite different (500 and 0.9 microns respectively).…”
Section: More Recent Optoelectronic and Electronic Hgte Devicesmentioning
confidence: 99%
“…Kim et al [89] were one of the first groups to look at the IR photoconductive properties of aqueous synthesized HgTe QDs in thin films. Citing the lack of a barrier presented by the capping ligand 1-TG to photogenerated hole extraction in their films (the HgTe/1-TG valence band offset is 0.33 eV) they suggested that HgTe photoconductivity would arise primarily from hole transport in the films, with the geminate photoelectrons remaining bound within the QDs.…”
Section: More Recent Optoelectronic and Electronic Hgte Devicesmentioning
confidence: 99%